1999
DOI: 10.1093/intqhc/11.5.407
|View full text |Cite
|
Sign up to set email alerts
|

The validity of self-reported diabetes quality of care measures

Abstract: Quality of care measures for diabetes are often drawn from a variety of sources. To the extent that data sources are biased, the measures can be misleading. Self-report is likely to lead to an overestimate of eye screening and the measurement of hemoglobin A1C. Reported rates of quality of care should be inspected carefully. The 'same' rate taken from different sources may vary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
4
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 3 publications
3
51
4
2
Order By: Relevance
“…However, this was a survey study, and potential flaws of survey research, including problems with nonresponse, inaccurate recall, and unrepresentative participants, have been previously described (14,15). Furthermore, it has been shown that selfreporting of screening measures by patients with diabetes is inaccurate (16).…”
mentioning
confidence: 99%
“…However, this was a survey study, and potential flaws of survey research, including problems with nonresponse, inaccurate recall, and unrepresentative participants, have been previously described (14,15). Furthermore, it has been shown that selfreporting of screening measures by patients with diabetes is inaccurate (16).…”
mentioning
confidence: 99%
“…However, there was an apparent discrepancy between agreement and the reliability measures of most tests and comorbids. The reasons for these discrepancies were discussed previously in detail [20,21].…”
Section: Discussionmentioning
confidence: 91%
“…However, agreement was moderate (k=0.37) in the Minnesota-USA study [20], in which findings demonstrated more over-reporting than underreporting of eye examinations by patients. This study found similar findings when comparing self-reports of an eye examination during the previous year with reported referral for eye examination (k=0.20).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although select studies have indicated that persons with diabetes can accurately report whether or not they have received an A1c test in the past year, 12 other studies indicate that self-reports of A1c tests overstate reality. 13 Future studies might investigate the accuracy of self-reports by following A1c adherence in a group of members with administrative claims data for their ability to accurately report the performance of an A1c test.…”
Section: Limitationsmentioning
confidence: 99%